The Ameliorative Potential of Vitamin E and Selenium on the Possible Adverse Effects of Azithromycin - Abdelaziz, Ahmed S.; Mabrouk, Zeinab A.; Ibrahim, Hosny A.; Khalifa , Hesham A. (Journal of Advanced Veterinary Research, 2023)
Azithromycin, an antibiotic belonging to the macrolide group, is used not only for bacterial infections, but also for fungal and viral diseases. The main side effects of its use are hepatic and renal toxicities. The present study was carried out to evaluate the possible ameliorative effect of vitamin E and selenium against azithromycin-induced hepatic and renal toxicities. Fifty male albino rats used were allocated into 5 equal groups, each of 10 rats. All the treatments were taken orally for ten days in all groups. Group I served as a normal control. Group II received olive oil. Group III received azithromycin (6mg/kg bwt). Groups IV and V received vitamin E and sodium selenite at doses of 100 mg/kg bwt and 0.3mg/kg bwt, respectively at two hours before azithromycin administration. Two blood samples were collected from each rat, one on heparin and the other without anticoagulant to obtain clear sera for hematological studies and biochemical analysis respectively. Liver and kidney tissues were collected for histopathological examination. Vitamin E or selenium administrations significantly decreased alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP) and Gamma- glutamyle transferase (GGT) activities, creatinine, urea and uric acid levels, and MDA concentration in azithromycin-treated rats. Moreover, both Vitamin E and selenium significantly increased hematological parameters, protein profile (total protein, albumin, and globulin) and antioxidant enzyme activities (GPX, SOD, GSH, CAT) in rats treated with azithromycin with a significant improvement in the histopathological pictures of the hepatic and renal tissues. Based on these findings, vitamin E and selenium may be beneficial agents for protection against liver and kidney toxicities induced by azithromycin.